2022
DOI: 10.1227/ons.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Frameless Robot-Assisted vs Frame-Based Awake Deep Brain Stimulation Surgery: An Evaluation of Technique and New Challenges

Abstract: BACKGROUND: Methodological approaches to deep brain stimulation (DBS) continue to evolve from awake frame-based to asleep frameless procedures with robotic assistance, primarily directed to optimize operative efficiency, lead accuracy, and patient comfort. Comparison between the 2 is scarce. OBJECTIVE: To analyze the impacts of methodological differences on operative efficiency and stereotactic accuracy using a frame compared with a frameless robotic platform while maintaining the awake state and use of multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our overall mean OR and procedural times, 272 and 145 minutes, respectively, were comparable with recently published studies using other robotic systems with mean OR times of 281 to 314 minutes and mean procedure times of 165 to 198 minutes. 18,38 In our experience, the robot-assisted procedure was significantly faster than the frame-based procedure. We also did observe an improvement in overall OR and procedure time from the beginning of our transition to robotic DBS to the end of this study because the last 10 cases were performed faster than the first 10 ( P = .03).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our overall mean OR and procedural times, 272 and 145 minutes, respectively, were comparable with recently published studies using other robotic systems with mean OR times of 281 to 314 minutes and mean procedure times of 165 to 198 minutes. 18,38 In our experience, the robot-assisted procedure was significantly faster than the frame-based procedure. We also did observe an improvement in overall OR and procedure time from the beginning of our transition to robotic DBS to the end of this study because the last 10 cases were performed faster than the first 10 ( P = .03).…”
Section: Discussionmentioning
confidence: 82%
“…36,37 Using the O-arm intraoperatively for robot registration eliminates time for transporting the patient to a CT scanner which has been noted to add significant time in previously described workflows. 38 Draping in the O-arm allows for rapid acquisition of a spin after placing the leads.…”
Section: Discussionmentioning
confidence: 99%
“…5,17-23 Four studies reported their use of a skull-mounted robot with optical array registration/navigation, with a target radial error of 1.12 ± 0.54 mm (n = 406 electrodes), operative time of 155.4 ± 36.5 minutes (n = 406), and total procedure time of 277.1 ± 38.2 minutes (n = 165). 7,24-26 Three studies (including this study) reported the use of a floor-mounted robot with a frameless transient fiducial array, with a target radial error of 0.84 ± 0.54 mm (n = 631 electrodes), operative time of 182.4 ± 47.8 minutes (n = 315), and total procedure time of 311.9 ± 63.0 min (n = 315). 27,28 One study reported their use of a floor-mounted robot with optical registration, and the only metric recorded was target radial error: 1.28 ± 0.37 (n = 60 electrodes).…”
Section: Resultsmentioning
confidence: 99%
“…In recent reports of errors achieved with other robot-assisted DBS, mean radial errors ranged from 0.6 to 1.7 mm and most studies comparing errors with the classic method showed better non-inferior outcomes in robot groups; the errors from other robot-based DBS surgeries are shown in Table 2 [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%